UMPSA prepares 17 buses for the benefit of 600 students heading home to celebrate Aidilfitri - Nor Salwana, Mohammad Idris (UMPSA, 2024)
PEKAN, 5 April 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is providing a total of 17 buses for approximately 600 students, thanks to the collaboration of the Department of Student and Alumni Affairs (JHEPA), the Department of Property Development and Management (JPPH), and the Student Representative Council (MPP).